Push factors and capital flows to emerging markets: Why knowing your lender matters more than fundamentals - Eugenio M. Cerutti; Stijn Claessens; Damien Puy (Asian Development Bank (ADB), 2017)
This paper analyzes the behavior of gross capital inflows across 34 emerging markets (EMs), including eight Asian economies. We first confirm that aggregate inflows to EMs comove considerably. Three findings are reported: (i) the aggregate comovement conceals significant heterogeneity across asset types as only bank-related and portfolio bond and equity inflows comove; (ii) while global push factors in advanced economies mostly explain the common dynamics, their relative importance varies by type of flow; and (iii) the sensitivity to common dynamics varies significantly across borrower countries, with market structure characteristics (especially the composition of the foreign investor base and the level of liquidity) rather than a borrower country's institutional fundamentals strongly affecting sensitivities. Countries relying more on international funds and global banks are found to be more sensitive to push factors. Our findings suggest that EMs need to closely monitor their lenders and investors to assess their inflow exposures to global push factors.
Keywords: F32; F36; G11; G15; G23; 330; capital flows; emerging markets; global banks; mutual funds; push factors